ANALISIS KINERJA PEGAWAI PAJAK YANG DIDETERMINASI OLEH SISTEM PERPAJAKAN DAN GAYA KEPEMIMPINAN: Studi Kasus Pada KPP Pratama Majalaya Bandung - Jayanthi Octavia; Reza Alpadizami (Jurnal Bina Bangsa Ekonomika, 2022)
This study discusses tax system and the leadership style on employee performance. Problems that occur in the Tax Office Pratama Majalaya Bandung in taxation system that still have weaknesses such as gray areas that make tax employees KPP Majalaya Bandung violate Rules of the tax system and a different style of leadership of each leadership in the service and supervision and not exactly in the selection of leadership styles. This study aims to test how the influence of tax system and leadership style on employee performance in Tax Office Pratama Majalaya Bandung. The research method used is descriptive analysis method verifikatif with quantitative approach with unit analyzed analysis is Tax Office Pratama Majalaya Bandung. And the population of 78 employees using saturated samples. Data analysis techniques used are descriptive and verification analysis assisted by smart software PLS 3.The result of the research shows that Tax system has significant effect on Employee Performance with positive relationship, Leadership style has a significant effect on Employee Performance with positive relationship